What Drives Rahn Adoption? - Egi Arvian Firmansyah; Arif Pratama; Abror; Muhammad Abdus Salam (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: Sharia pawning, or Rahn, is one of the Islamic financial products adopted by society to solve cash needs and have assets as collateral. Adoption of this product is limited in scholarly work. This study examines the effects of religiosity, service quality, and location on adopting Islamic (Sharia) pawning services. Design/Methods/Approach: A self-administered questionnaire was distributed to 200 Islamic bank customers. Both offline and online questionnaires were employed for data collection. SPSS 22 and SmartPLS 4.0 software were used to perform comprehensive data synthesis, confirmatory factor analysis, and rigorous hypothesis testing, fostering a data-driven approach to ensure the integrity and validity of this research. Findings: The results show that only religiosity has a significant relationship with Rahn adoption. Location and service quality do not drive customers to use Rahn products. These results indicate the significant role of religious values in Rahn adoption. Originality/value: This study contributes to the limited Islamic marketing literature on Rahn or Sharia pawnshops, primarily on the determinant of this financing adoption using the Indonesian context. Practical/policy implications: Islamic pawnshops must emphasize Sharia compliance in the Rahn product provision because customers, primarily those in relatively religious regions, highly consider this aspect when using the pawnshop service.